BML-260 Promotes the Growth of Cord Blood and Mobilized Peripheral Blood Hematopoietic Stem and Progenitor Cells With Improved Reconstitution Ability - Albayrak, Esra; Akgol, Sezer; Turan, Raife Dilek; Uslu, Merve; Kocabas, Fatih (Wiley, 2022)
Hematopoietic stem cells (HSCs), which are multipotent and have the ability to self-renew, are frequently used in the treatment of hematological diseases and cancer. Small molecules that target HSC quiescence regulators could be used for ex vivo expansion of both mobilized peripheral blood (mPB) and umbilical cord blood (UCB) hematopoietic stem and progenitor cells (HSPC). We identified and investigated 35 small molecules that target HSC quiescence factors. We looked at how they affected HSC activity, such as expansion, quiescence, multilineage capacity, cycling ability, metabolism, cytotoxicity, and genotoxicity. A transplantation study was carried out on immunocompromised mice to assess the expanded cells' repopulation and engraftment abilities. 4-[(5Z)-5-benzylidene-4-oxo-2-sulfanylidene-1,3-thiazolidin-3-yl]benzoic acid (BML)-260 and tosyl-l-arginine methyl ester (TAME) significantly increased both mPB and UCB-HSPC content and activated HSC re-entry into the cell cycle. The improved multilineage capacity was confirmed by the colony forming unit (CFU) assay. Furthermore, gene expression analysis revealed that BML-260 and TAME molecules aided HSC expansion by modulating cell cycle kinetics, such as p27, SKP2, and CDH1. In addition to these in vitro findings, we discovered that BML-260-expanded HSCs had a high hematopoietic reconstitution capacity with increased immune cell content after xenotransplantation into immunocompromised mice. In addition to the BML-260 molecule, a comparison study of serum-containing and serum-free chemically defined media, including various supplements, was performed. These in vitro and xenotransplantation results show that BML-260 molecules can be used for human HSC expansion and regulation of function. Furthermore, the medium composition discovered may be a novel platform for human HSPC expansion that could be used in clinical trials.
Kocabas, Fatih/0000-0001-8096-6056; Akgöl, Sezer/0000-0002-3154-3214; Uslu, Merve/0000-0002-5410-7052;
Keywords: Expansion; Hematopoietic Stem Cells; HSCT; Quiescence